The Relationship between Leptin Levels and Continuous Positive Airway Pressure Treatment: A Cluster Analysis - Takashi Oki; Yutaka Kozu; Mamiko Hoshi; Yasunori Itoda; Naho Furusho; Ryosuke Ozoe; Yusuke Jinno; Akifumi Hirata; Yusuke Kurosawa; Shiho Yamada; Asami Fukuda; Mari Hikichi; et al. (Sleep Science)
Objective Leptin is an appetite-suppressing hormone released by adipose tissue that plays an important role in severe obstructive sleep apnea syndrome (OSAS). However, it is unclear whether leptin levels are a useful biomarker for this syndrome. The present study aimed to assess the effect of continuous positive airway pressure (CPAP) treatment on the syndrome according to leptin levels, using a cluster classification based on clinical features of the syndrome.